Airway Remodeling in Asthma - Hough, Kenneth P.; Curtiss, Miranda L.; Blain, Trevor J.; Liu, Rui-Ming; Trevor, Jennifer; Deshane, Jessy S.; Thannickal, Victor J. (Frontiers in Medicine, 2020)
Asthma is an inflammatory disease of the airways that may result from exposure to allergens or other environmental irritants, resulting in bronchoconstriction, wheezing, and shortness of breath. The structural changes of the airways associated with asthma, broadly referred to as airway remodeling, is a pathological feature of chronic asthma that contributes to the clinical manifestations of the disease. Airway remodeling in asthma constitutes cellular and extracellular matrix changes in the large and small airways, epithelial cell apoptosis, airway smooth muscle cell proliferation and fibroblast activation. These pathological changes in the airway are orchestrated by crosstalk of different cell types within the airway wall and submucosa. Environmental exposures to dust, chemicals and cigarette smoke can initiate the cascade of pro-inflammatory responses that trigger airway remodeling through paracrine signaling and mechanostimulatory cues that drive airway remodeling. In this review, we explore three integrated and dynamic processes in airway remodeling: (1) initiation by epithelial cells; (2) amplification by immune cells; and (3) mesenchymal effector functions. Furthermore, we explore the role of inflammaging in the dysregulated and persistent inflammatory response that perpetuates airway remodeling in elderly asthmatics.